Respuesta :

Answer:

Step-by-step explanation:

Arithmetic sequaence:

[tex]\sf a_n = -3(4)^n - 1\\\\a_1=-3*4^1 -1\\\\ = -3*4 - 1\\\\ = -12 - 1\\\\a_1=-13[/tex]

[tex]a_2 = -3*4^2-1\\[/tex]

    = -3*16 -1

     = -48 - 1

    = -49

difference = second term - first term

                 = -49 -(-13)

                = -49 + 13

             d = -36

[tex]\boxed{S_n=\dfrac{n}{2}[2a + (n-1)d]}[/tex]

[tex]\sf S_5=\dfrac{5}{2}*[2*(-13} + 4*(-36)]\\\\ =\dfrac{5}{2}[-26-144]\\\\=\dfrac{5}{2}*(-270)[/tex]

= 5*(-135)

= -675